When a Good Thing Becomes a Better Thing: The Role of Lateral Display in Upcycled Product Advertisements. Issue 4 (3rd August 2022) - Kim, Junghyun; Kim, Youngju; Kwon, Junbum
Abstract: An upcycled product—a new product created from reused waste materials—has two identities: a past identity derived from the source materials and a present identity associated with the product's current value. This research investigates how the lateral display of an upcycled product's past identity relative to its present identity changes consumers' evaluations of upcycled product advertisements and their word-of-mouth (WOM) intentions. Across four studies, including an eye-tracking experiment, we demonstrate that consumers evaluate an upcycled product advertisement more (vs. less) favorably when the product's past identity is presented to the left (vs. the right) of its present identity, which, in turn, affects consumers' WOM on social media. We suggest that this lateral display effect is driven by consumers' spatial representation of time. Our research carries managerial implications for marketing professionals who want to effectively advertise their upcycled products and contributes to the literature on upcycling by demonstrating the role of past-identity location in upcycled product advertisements.